Teacher’s Feedback in Teaching Writing of Narrative Texts to the Tenth Grade Students of SMAN 3 Nganjuk (RETAIN, 2013)
Writing skills is considered the most difficult skill. The students usually face many difficulties in exploring the ideas or even finding the appropriate words to what they want to write. In this research, the researcher focuses on giving teachers’ written feedback in teaching writing narrative texts to the tenth graders of SMAN 3 Nganjuk. Written feedback is taken to provide an interaction between students’ writing and the teacher. In this process a teacher read the students’ work and responds to it through some written comments. Based on the background, the researcher did a research in SMAN 3 Nganjuk. The subjects of the study were the students of X-2. There were 33 students, 13 male and 20 female students. The researcher takes this grade because based on SI; one of the language skills that must be achieved is a writing skill. In addition, a writing narrative text is taught in this grade. This study is descriptive qualitative. The instruments that are used by the researcher are observation checklist, field notes, and students’ written works. Based on the analysis data, the researcher collected the data from three observations. The first observation, the writing task was given to check the understanding of the students in writing narrative text, but the teacher didn’t give feedback. In the second and third observations feedback were given. In the second observation, the writing task was done in groups. Meanwhile in the third observation, it was done individually. The researcher analyzed the students’ written works that had been given written feedback from the teacher. In order to describe how the students write a narrative text based on the elements of writing. The students’ written works were analyzed by ESL Composition Profile. Those were described whether its categories were very good, good, fair, and poor level. Teachers’ written feedback was considered as an appropriate way in teaching writing a narrative text because it could motivate the students to write a narrative text. Furthermore, by giving teacher’s written feedback, the students made progress in writing narrative text. It could be seen from the results of students’ narrative writing result. There were progress of the results of the students’ writing in terms of content, organization, vocabulary, language use and mechanic. It can be concluded that teacher’s written feedback helps the students write a narrative text. It is because the teacher gives the feedback clearly, and also one by one. It consists of how the students write the generic structures and language features of narrative texts, the tenses that the students use in their writing work, choosing the appropriate words/ diction, punctuation. It makes the students know and understand their mistakes in writing a narrative text easily. Finally, the students become interested in the teaching and learning process. Key Words: Teacher’ Written Feedback, Writing, Narrative text, Students’ Written Work Abstrak Ketrampilan menulis dianggap sebagai ketrampilan yang paling sulit. Siswa biasanya menghadapi banyak kesulitan mengungkapkan idea atau pemilihan kata yang tepat yang akan mereka tulis. Penelitian ini Fokus pada feedback dari guru di dalam pembelajaranb menulisa narrative teks untuk siswa kelas sepuluh dari SMAN 3 Nganjuk. Feedback disediakan sebagai interaksi di antara pekerjaan siswa dan guru. Dalam proses ini seorang guru membaca pekerjaan siswa da meresponnya melalui beberapa komen. Berdasarkan latar belakang yang ditulis, peneliti melakukan sebuah penelitian di SMAN 3 Nganjuk. Peserta penelitian ini adalah siswa kelas X-2. Ada 33 siswa, 13 laki-laki dan 20 perempuan. Peneliti mengambil kelas ini karena berdasarkan SI; salah satu ketrampilan bahasa yang harus dicapai di kelas sepuluh adalah ketrampilan menulis. Penelitian ini adalah descriptive qualitative. Alat yang digunakan oleh peneliti adalah observation checklist, Fielf note, hasil pekerjaan siswa. Berdasarkan data analisis, peneliti mengumpulkan data dari 3 observasi. Observasi yang pertama, tugas menulis diberikan hanya untuk mengecek pemahaman siswa pada kemampuan menulis narrative teks, tetapi guru tidak memberikan feedback. Pada observasi yang kedua dan ketiga guru memberikan feedback. observasi yang kedua tugas menulis di lakukan secara berpasangan. Sedangkan di obnservasi yang ketiga dilakukan secara individu. Peneliti menganalisis pekerjaan siswa yang sudah diberikan feedback dari guru. Dengan tujuan untuk mendeskripsikan bagaimana siswa menulis narrative teks berdasarkan unsure- unsur dari menulis. hasil tulisan siswa dianalisis dengan menggunakan rubric ESL composition profile. Itu dideskripsikan apakah termasuk dalam level yang sangat bahus, bagus, sedang lemah. Feedback dari giuru dapat dikatakan sebagai cara yang tepat dalam pengajaran menulis narrative teks karena itu dapat memotivasi siswa- siswa untuk menulis narrative teks. Lebih-lebih dengan memberikan feedback dari guru siswa ada peningkatan dalam menulis narrative teks. Hasil dari siswa menulis dalm bentuk isi, organisasi, vocabulary,bahasa yang digunakan dan mechanic mengalami peningkatan. Itu dapat disimpulkan bahwa feedback dari guru membantu siswa dalam menulis sebuah narrative teks. Itu dikarenakan guru memberikan feedback dengan jelas dan satu persatu. Itu terdiri dari bagaimana siswa menulis generic structure dan language feature dari narrative teks, tense yang digunakan dalam pekerjaan mereka, pemilihan kata yang tepat. pemberian tanda baca. Itu membuat siswa mengetahui dan mengerti kesalahan mereka dalam menulis narrative teks dengan mudah. Akhirnya siswa- siswa menjadi tertarik pada proses berlangsunganya pembelajaran. Kata Kunci: Feedback Guru, Menulis, Narrative, Pekerjaan menulis siswa